2015
DOI: 10.1002/ps.4100
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal glycoalkaloids: chemical defence of edible African nightshades against the tomato red spider mite, Tetranychus evansi (Acari: Tetranychidae)

Abstract: Our results suggest that the presence of SGAs may play a key role in the differential defence of edible African nightshades against attack by T. evansi. These findings may add to the plethora of environmentally friendly tools from natural plant products for management of T. evansi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…However, S. sarrachoides was recently shown to have active components, i.e. stereoidal glycoalkaloids, that reduce T. evansi survival . The Solanaceae specialization of T. evansi could also explain their different dispersal strategies, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, S. sarrachoides was recently shown to have active components, i.e. stereoidal glycoalkaloids, that reduce T. evansi survival . The Solanaceae specialization of T. evansi could also explain their different dispersal strategies, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl ketones such as 2-undecanone and non-volatile glucose esters have been found to deter settling of the potato aphid, Macrosiphum euphorbiae Thomas [14]. In line with these findings, some researchers have suggested that the presence of glandular trichomes in certain plants may indicate potency of internal leaf chemistry against herbivore establishment and performance [1820]. On the other hand, some studies have shown that not all insect species are deterred by these secretions as reported for the mirid bug, Tupiocoris notatus Distant (Heteroptera: Miridae), which is specifically adapted to these unique secretions [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is largely unknown which terminal plant defenses determine resistance or susceptibility to mites, negative correlations were found between mite fitness and several plant secondary metabolites (18,(25)(26)(27). How plants detect spider mite feeding is poorly understood, but analyses of transcriptional networks have suggested the involvement of receptor-like kinases reminiscent of other plant-herbivore interactions (28).…”
mentioning
confidence: 99%